Application of the Teaching Games for Understanding Learning Model to Improve Basic Passing Technical Ability in Volleyball Games - Awaludin, Eja; Indrayogi, Indrayogi; Suryadin, Tatang (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
The basic passing technical skills of students at MTS PUI Kancana are still below the KKM score, this is the basis for this research as an effort to improve student learning outcomes. The method used is Classroom Action Research, for the sample, namely all 21 students. This Classroom Action Research was carried out in two stages, namely Cycle I and Cycle II. The results of the research are from the first cycle at the first meeting the average value is 1.90 and at the second meeting the average value is 2.71. While the results of the second cycle at the first meeting the average value was 3.38 and at the second meeting the average value was 3.66, each meeting experienced a pretty good increase. The implementation of improving teacher learning activities went quite well with a teacher activity score of 2.42 (on a scale of 1-5) in the first cycle of the first meeting and the second meeting became 4.28. Whereas in cycle II the value of teacher activity increased learning achievement from round I was 3.57 and round II was 4.71. The results of the learning test average value obtained in the implementation of the evaluation of student learning improvement in cycle I was 72 with the number of students who had not completed 5 people while those who had completed were 16 students out of 21 students. While the average value obtained in the implementation of learning improvements in cycle II is 75 and 20 students have achieved completeness and 1 student has not completed. Based on the results of the study, it can be concluded that the TGfU approach can improve the basic techniques of passing volleyball for MTs PUI Kancana students